2019
DOI: 10.1155/2019/7927914
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infection following Total Elbow Arthroplasty

Abstract: A specific treatment protocol for managing fungal infections after total elbow arthroplasty (TEA) does not currently exist. The purpose of this report is to describe our experience and outline our treatment algorithm for a rare case of prosthetic joint infection (PJI) following a TEA. We present a case of a PJI due to Candida parapsilosis after TEA in a 57 year-old Caucasian woman with a history of hypertension, depression, and three previous surgical procedures to the affected limb. A fungal PJI by the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [ 12 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], small case series [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [ 12 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], small case series [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ...…”
Section: Resultsmentioning
confidence: 99%
“…Most cases exhibit subtle inflammatory symptoms, [33] while only a few present as acute infections that can be diagnosed in the early stage. [34][35][36][37][38][39] Initial diagnostic tools for fPJI include ESR and CRP, as serum inflammatory biomarkers are easily accessible worldwide, cost-effective, and can be routinely performed preoperatively. These markers can serve as the first indicators for PJI in the absence of clinical signs.…”
Section: Diagnosismentioning
confidence: 99%